Enhanced electrical and photosensing properties of pentacene organic thin-film phototransistors by modifying the gate dielectric thickness - Kwon, Jae-Hong; Chung, Myung-Ho; Oh, Tae-Yeon; Ju, Byeong-Kwon; Yakuphanoğlu, Fahrettin (Elsevier, 2010)
The effects of dielectric layer thickness on the electrical performance and photosensing properties of organic pentacene thin-film transistors have been investigated. To improve the electrical performance of pentacene thin-film transistors (TFTs), the poly-4-vinylphenol (PVP) polymer with various thicknesses was used in fabrication of the pentacene transistors. The pentacene thin-film transistor with the PVP dielectric layer of 70 nm exhibited a field-effect mobility of 4.46 cm(2)/Vs in the saturation region, a threshold voltage of -4.0 V, a gate voltage swing of 2.1 V/decade and an on/off current ratio of 5.1 x 10(4). In the OFF-state, the photoresponse of the transistors increases linearly with illumination intensity. The pentacene transistor with the thinner dielectric layer thickness indicates the best photosensing behavior. It is evaluated that the electrical performance and photosensing properties of pentacene thin-film transistors can be improved by using various thickness dielectric layer. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Thin-film transistor; Pentacene; Photosensing